Representation of Forest in the Poems of Jacinta Kerketta: An Ecocritical Perspective - Malwika (Literary Studies, 2024)
Forest has often been employed as imagined spaces in narratives of various kinds and different cultures. Literature of any culture is an expression of its cultural attitudes, values, and beliefs. The non-human world is a significant part of human life and culture. However, a dualistic approach treating nature and culture as binary opposites has become prevalent in modern times. This approach is inherently flawed and leads to a discourse stripping nature of its agency. Jacinta Kerketta belongs to one of the important tribes, inhabiting the Chota Nagpur plateau of the Indian subcontinent and its adjoining regions, named the Oraon tribe. Her poems present a discourse of tribal worldview where humans identify themselves with the non-human world surrounding them. This biocentric identification with one’s environment is important as we are part of various ecosystems. The paper seeks to highlight the same with the help of select verses along with the analysis of the representation of forest from various perspectives. It also foregrounds the various contemporary issues prevalent in tribal societies like deforestation, cultural amnesia, etc., and presents a critique of capitalism. The paper employs an ecocritical theoretical framework for the analysis of the select poems from her two Poetry Collections titled Angor (2016) and Land of the Roots (2018)